Etnis Tionghoa Dan Politik Studi Kasus Elit Etnis Tionghoa Dalam Kepengurusan Partai Politik Pdi-P Dan Gerindra Di Kota Semarang Periode 2009-2014 - Yusuf Rahmat; Purwoko .; Ahmad Taufiq (Journal of Politic and Government Studies, 2013)
The reason why the writer focuses on this study is the political of Tionghoa in a structure of political party in kota Semarang period 2009 until 2014 there is an interesting phenomenon because Tionghoa joining in a political activities. Another condition, which tend to better in condition.The purpose of this study is that the writer would like to catch and to explain elite politics behavior of Tionhoa about the existence of this ethnic in managing Gerindra Party and PDI-P in Semarang. Beside, the writer would like to see the whether there is a correlation between political background of Tionghoa, its contribution and function in a political party, and also the problem found in organizing internal or external party of gerindra or PDI-P in SemarangThe method user by the writer is qualitative research, in term of snow ball method and structural interview guide as one of the technique in collecting data. The Writer gave his general poin of view as the result of the whole content of questionarries and analyzing interviewing as a method based on someone’s interpretation that give a real description of elite politic behaovior of Tionghoa in Semarang at this present reformation eraThe result of this study showed that Tionghoa elite politic joining in political party is a sociological base a the leader of those parties, family and friends support. The joining of political actor of tionghoa in social activity is still low. Tionghoa political actors in political structure are tend to economical side. Tionghoa polical actors should be able to see that politic is not only as someone’s side job but also a kind of serious duty and long term oriented to develop its potential function seriously when choosing the actors from their strategically position.Key word : elit Politic, Tionghoa, political party, political structure, gerindra and PDI-P